METODE PENANGANAN PASIEN GANGGUAN JIWA DI PONDOK PESANTREN AL-BAJIGUR TENONAN MANDING - Ahmad Sulaiman; Bagus Amirullah (Al-Amien Prenduan University, Sumenep, 2020)
Along with the development of science and technology that has led people to modern civilization, it has also made them experience changes in values and orientation of life is quite significant. One of the implications for the existence is the change of lifestyle that comes from the values and teachings of religion that put forward fraternity, cooperation, kinship. The formulation of this research problem is, how the method of handling mental patients in Pondok Pesantren Al-Bajigur Tenonan District Manding.Based on the title of this study, the researchers used a qualitative approach in case studies because it is done intensive, against a particular organization or institution. That is the method of handling mental patients in Pondok Pesantren Al-Bajigur Tenonan District Manding.Adapum data collection techniques in this study using observation and interviewing guidelines. The results showed that the method penanga nan mental patients in boarding school Al-Bajigur Tenonan Manding District has several methods of healing that is (1) the method of prayer, that is by the patient prayed by the therapist and when istighosah time, (2) bathing method, yaitudengan bathing the patient in the bath pool (3) introduction method with nature, that is by introducing patient with nature by social interaction as well as farming and cultivating. (4) Quran teaching method that is, method by way of recited Al-Qur ' (5) method of prayer water ', that is by the way the patient is in water with prayer that has been read in prayer. However, in this method of handling of mental disorders there are some obstacles that inhibit the smoothness of the method of handling mental patients in antranya: lack of economy and less responsibility of the patient's family.